NATIONAL IDENTITY AS A FACTOR OF STATE SECURITY - Zamiralova,; Karpunina,; Shimanovskaya, (Revista Inclusiones, 2020)
The article highlights such an urgent problem as ensuring the national security of the state. It is necessary to form a national identity to resist internal and external threats. The authors define this category and analyze its structure. Based on the results of the study, conceptual conclusions are formulated on the formation of policies that contribute to national security through the formation of national identity.